Численный анализ динамических процессов в неоднородных пьезокерамических цилиндрах (обзор) - Григоренко, А.Я.; Григоренко, Я.М.; Лоза, И.А. (Прикладная механика, 2020)
В статье проведено решение широкого класса задач пространственной теории электроупругости о гармонических волновых и колебательных процессах в кусочно неоднородных и непрерывно неоднородных пьезокерамических телах цилиндрической формы. Проведен анализ влияния фактора неоднородности связанного электрического поля и вида предварительной поляризации пьезокерамических материалов на спектральные характеристики указанных выше электроупругих тел. Для этого был предложен дискретно континуальный численно аналитический подход к решению широкого класса задач пространственной теории электроупругости о стационарных динамических процессах в кусочно-неоднородных (слоистых) и непрерывно неоднородных (функционально градиентных) телах цилиндрической формы. Ранее такой подход эффективно применялся при решении задач теории упругости. Представлений огляд робіт присвячено чисельним дослідженням нових задач теорії електропружності. А саме визначенню динамічних характеристик неоднорідних п'єзокерамічних хвилеводів кругового поперечного перерізу та неоднорідних п'єзокерамічних циліндрів скінченної довжини. Для розв'язання описаних задач запропоновано ефективний чисельно-аналітичний підхід. Запропонований підхід базується на поєднанні різноманітних аналітичних перетворень (апарату спеціальних функцій, розвиненню в ряди Фур'є та методу сплайн-колокацій), які дозволяють звести вихідні тримірні рівняння теорії електропружності у частинних похідних до граничної задачі на власні значення для систем звичайних диференціальних рівнянь. Отримана система звичайних диференціальних рівнянь розв'язується методом дискретної ортогоналізації. На основі отриманих розв'язків проведено дослідження закономірностей спектральних характеристик в неоднорідній структурі з врахуванням зв'язаного електричного поля п'єзокерамічних шарів. Проведено також дослідження впливу неоднорідності та зв'язаного електричного поля на динамічні характеристики описаних вище тіл. Значну увагу надано дослідженню достовірності отриманих чисельних обчислень. The review of works is given, which are devoted to the numerical investigations of the new problems of the theory electroelasticity. Namely, they are devoted to the determination of dynamical characteristics of the inhomogeneous piezoceramic circular waveguides and the inhomogeneous piezoceramic finite-length cylinders. An effective numerical-analytical approach is proposed in these works. The proposed method is based on uniting the different analytical transforms (apparatus of special functions, expansion in the Fourier series, and spline-approximations method with collocation method) allows reducing the initial three-dimensional equations of electroelasticity theory in the partial derivatives to the boundary value problem for the system of ordinary differential equations. The obtained one-dimensional problem is solved by the method of discrete orthogonalization. Basing on the obtained solutions, the new regularities of spectral characteristics with the inhomogeneous structure are studied, with allowance for the coupled electric field of the piezoceramic layers. Also, the study is carried out for an effect of the inhomogeneity and coupled electric field on the dynamic characteristics of the bodies under study. Significant attention is paid to the validation of the reliability of the results obtained by the numerical calculations.